Postdoctoral Fellowship Program in Educational Research. Final Report - Pierce, Douglas R.; California Univ., Berkeley ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This document describes the postdoctoral training program undertaken by Douglas R. Pierce at the University of California, Berkeley. He summarizes his major activities and presents a conclusion based on the year of advanced study. (JS)
Contract Number: OEG-0-8-980784-4670.
Educational level discussed: Higher Education.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Research; Graduate Study; Higher Education; Postdoctoral Education; Research; University of California Berkeley